Foreign Currency Loans and Loan Arrears of Households in Central and Eastern Europe - Elisabeth Beckmann; Jarko Fidrmuc; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2012)
Given recent adverse developments, widespread foreign currency borrowing in CEECs poses a serious challenge for financial stability. Against this background, we use survey data to study the determinants of loan arrears of private households. Our data confirm a non-negligible impact of foreign currency loans on financial vulnerability. However, higher loan delinquency rates in depreciation countries can only partly be explained by foreign currency borrowing. Employing survey information about the reasons for households' financial difficulties, we show that income shocks exert a stronger impact on loan delinquency rates than the direct effect which works through increased installments on foreign currency loans.
Keywords: G21; D14; C25; 330; Foreign currency loans; arrears; dollarization; euroization; household debt; non-performing loans; financial vulnerability; CEECs; Verbraucherkredit; Währungsrisiko; Währungssubstitution; Private Verschuldung; Notleidender Kredit; Finanzkrise; Ostmitteleuropa